A Comment On The Interdisciplinary Approach To Administrative Thought - Sarachek, Bernard (Academy of Management Journal, 1967)
Interdisciplinary approaches to administration may foster prescientific biases influencing the concepts that theorists develop or judge to be legitimate. This article discusses some of these biases.